Farm productivity and rural poverty in India - Datt, Gaurav; Ravallion, Martin (International Food Policy Research Institute, 1998)
To what extent do India’s rural poor share in agricultural growth? Combining data from 24 household sample surveys spanning 35 years with other sources, we estimate a model of the joint determination of consumption-poverty measures, agricultural wages, and food prices. We find that higher farm productivity brought both absolute and relative gains to poor rural households. A large share of the gains were via wages and prices, though these effects took time. The benefits to the poor were not confined to those near the poverty line.